Indicators of social-comparison jealousy - Lepeshko, Kseniya V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Social-comparison jealousy arises under the condition of the high importance of the situation of social comparison and is characterized by a set of related thoughts about undeserved, injustice, wrongness and bias of the existing advantages of another individual, a set of experiences of negative emotions (primarily anxiety, sadness, anger, disgust, contempt) and readiness for action aimed at coping with the situation with the help of strategies of self-improvement, equalization or evasion. It was found that there is a need to develop indicators of social-comparison jealousy. Following a three-component structure of social-comparison jealousy that includes cognitive, affective and behavioral components, it was assumed that such indicators can be cognitive, emotional and behavioral assessments. The aim of the study was to develop empirical indicators of social-comparison jealousy; 195 respondents (aged 18 to 45 years) took part in the study. As a tool of the study method of assessing the situation of provocation of social-comparison jealousy was used. Statistical processing was carried out by the program SPSS 13.0 (for Windows). It effectuated Pearson correlation analysis and factor analysis by principal component method with Varimax-rotation for calculate the indices of social-comparison jealousy. Correlation analysis of cognitive assessments has shown that scales that evaluate cognitive social-comparison jealousy have a positive strong and moderate relationship with each other. The principal component factor analysis identified two factors: the first the criteria of merit, justice and correctness, and the second – objectivity. Correlation analysis of emotional assessments revealed that a number of scales evaluating emotional social-comparison jealousy, have a strong and moderate positive relationship with each other, and the negative relationship between the emotions of anger and joy, sadness and joy. Factor analysis identified four factors: the first factor included emotions of fear, shame and guilt; the second one – anger, disgust, contempt; the third one – exciteman and surprise; the fourth – joy and sorrow. Correlation analysis of behavioral assessments allowed to establish that all scales have a negative relationship with each other, that is why they should be considered as three different behavioral strategies. The factor analysis identified two factors: the first with the highest factor loads, but opposite signs included the reactions of ascending comparisons and withdrawal, the second – the reactions of lateral comparisons. Based on the obtained results, the indices of cognitive and emotional social-comparison jealousy were calculated, as well as three indices of behavioral reactions, were presented by formulas for i situation and for n situations.
Keywords: social-comparison jealousy; cognitive social-comparison jealousy; emotional social-comparison jealousy; indicators of jealousy